Etiopathogenesis of lacrimal sac mucopeptide concretions: insights from cinematic rendering techniques - Mohammad, Javed Ali; Scholz, Michael; Singh, Swati; Heichel, Jens; Paulsen, Friedrich (Graefes Archive For Clinical and Experimental Ophthalmology, 2020)
Background/aim: To investigate the structural features following the cinematic rendering of lacrimal sac mucopeptide concretions (MPC). Methods: The study was performed on five mucopeptide concretions obtained from the lacrimal sac during dacryocystorhinostomy. All the concretions were imaged using special protocols of CT scans to obtain ultra-thin slices. Cinematic rendering (CR) techniques (Siemens Healthineers AG, Erlangen, Germany) were utilized to allow real-time computation of the interaction of photons and scanned patient images using the Monte Carlo path tracing algorithms. The CR algorithms facilitated volumetric reconstruction of the mucopeptide concretions to visualize the texture and inner structures. Each concretion could be sliced and viewed at 100-μm intervals. False color display and the use of different transfer functions were utilized to display variable densities of the concretions in color during visualization. Images obtained by virtual camera were further analysed to assess the structural features. Results: The 3D cinematic rendered images of MPC showed uniform structural consistency on the surface and minimal heterogeneity from the surface up to the core. As the image slicing occurs towards the core, a well-defined structure of grossly different consistency (nidus) from the rest of the MPC was noted. This area was usually located in the paracentral region and constitutes approximately < 10% of the entire area. If a color display was assigned to the internal structure of the MPC, most of it appears to be compact and dense but the density reduces in the periphery of the nidus and delineates it well. Further structural enhancements with the 3D cinematic rendering in some MPCs demonstrate occasional 1–2 more areas with similar features as that of nidus. Conclusions: 3D CR is a useful modality to study the internal structure of MPC. The CR findings also provide further evidence to support the earlier etiopathogenesis theory based on ultrastructural and immunohistochemistry features.
CRIS-Team Scopus Importer:2020-06-26
Keywords: 3D; Concretion; Dacryolith; Lacrimal; Lacrimal sac; Mucopeptide